Acetylsalicylic acid and its application in disease prevention in postmenopausal women - Połać, Ireneusz; Boryczka, Katarzyna; Bijak, Michał; Borowiecka, Marta; Wojsiat, Joanna; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2011)
Acetylsalicylic acid (ASA) is a simple chemical compound belonging to a group of nonsteroidal anti-inflammatory drugs (NSAIDs). The mechanism of acetylsalicylic acid is based on the inhibition of cyclooxygenase (COX). That enzyme is responsible for the biosynthesis of cyclic prostanoids, i.e. prostaglandins (D2, E2, F2, I2), thromboxane A2 (TXA2) and prostacyclin. For this reason ASA is one of the most popular anti-inflammatory drugs present on the pharmaceutical market. Due to its ability to inhibit the synthesis of TXA2 (molecules capable of platelet activation) ASA is effective in the prevention of cardiovascular diseases such as ischemic heart disease. Clinical trials confirm the efficacy of aspirin in the prevention of cardiovascular diseases in postmenopausal women. In some cases ASA is unable to inhibit platelet activation. This phenomenon is called aspirin resistance. Acetylsalicylic acid can also inhibit aromatase activity, therefore it may be used in the prevention of breast cancer. Many clinical trials confirm that acetylsalicylic acid reduces the risk of breast cancer in postmenopausal women. Use of ASA may also increase bone mineral density (BMD). This article describes the mechanism of action and pharmacokinetics of the acetylsalicylic acid as well as clinical trials conducted on postmenopausal women.